Medication management in the context of mental illness: an exploratory study of young people living in Australia - Sara S. McMillan; Victoria Stewart; Amanda J. Wheeler; Fiona Kelly; Helen Stapleton (BMC, 2020)
Abstract Background Young people face significant challenges when managing a mental illness, such as acquiring treatment autonomy, being inexperienced users of the healthcare system and associated peer-related stigma. While medication use can be challenging in its own right, there is comparatively little information about the associated experiences and needs of young people with mental illness, particularly in the Australian context. This exploratory study will provide valuable insight into how this group is currently supported in relation to medication use. Methods Young people (aged 14-25 years) who had used a prescription medication for any mental illness for a minimum of 2 months were eligible to participate in this qualitative exploratory study. Semi-structured interviews were conducted between October 2017-September 2018 in consultation rooms at two youth-focused mental health support organisations in Brisbane, Queensland. Interview questions explored how participants managed their medication and related experiences. Interviews were transcribed verbatim and descriptively analysed using thematic analysis. Results Eighteen young people discussed their lived experience during interviews averaging 50 min in duration. Finding the right medication that reduced symptom severity with minimal side-effects was identified as a complex experience for many, particularly when there was a lack of information, support or reduced financial capacity. Young people described a range of strategies to manage medication side-effects, changes and to support routine medication use. Conclusions Young people persevered with taking medication to manage a mental illness within a healthcare system that does not adequately support this vulnerable population. There remains a clear directive for healthcare professionals to provide credible information that proactively engages young people as healthcare participants, and for policy makers to consider financial burden for this population with limited financial capacity.